Validation of a New Histopathologic Risk Model in Early Oral Tongue Cancer: A Combination of a Modified Worst Pattern of Invasion and a New Tumor Budding Score - Almangush, Alhadi; Salo, Tuula; Haglund, Caj; Kowalski, Luis Paulo; Hagström, Jaana; Coletta, Ricardo D; Mäkitie, Antti A; Leivo, Ilmo (United States, 2025)
Oral tongue squamous cell carcinoma (OTSCC) is the most common cancer of the oral cavity. A new histopathologic risk assessment has been recently introduced and we sought to validate its prognostic value in a large multicenter cohort of early-stage OTSCC. A total of 310 cases treated for early-stage OTSCC were included in this study. The assessment of modified worst pattern of invasion and a recently developed tumor budding score were performed in hematoxylin and eosin-stained sections. A statistically significant association was observed in the multivariable analysis between high score of the new risk model and worse disease-specific survival (HR: 2.54, 95% CI: 1.48-4.37, P<0.001). Similarly, in disease-free survival, the high-risk group was significantly associated with poor survival (HR: 1.66, 95% CI: 1.07-2.58, P=0.024). In conclusion, the new histopathologic risk model is a powerful prognostic indicator and can be assessed as part of routine diagnostic practice. Early-stage OTSCC patients with a high-risk score have a poor prognosis and therefore require a multimodality treatment strategy with a close clinical follow-up.